pI-Control in Comparative Fluorescence Gel Electrophoresis (CoFGE) using amphoteric azo dyes - Hanneken, Marina; Šlais, Karel; König, Simone (Data in brief, 2015)
Amphoteric azo dyes were used for internal control of pI values in Comparative two-dimensional Fluorescence Gel Electrophoresis (CoFGE) [1]. The 2D-gel images of separated Escherichia coli proteins as well as those of colored amphoteric dyes separated by isoelectric focussing are presented. The latter were used to correct for variation in the first electrophoretic dimension and further improve protein coordinate assignment in 2D-gel electrophoresis. Data tables are supplied to demonstrate pI-value calibration and the effect on the assignment of protein spot coordinates.
Keywords: Gel electrophoresis; pI; 2D-PAGE; CoFGE